(3af GdEOGQI HGdCacGQs - (3cQjSJha aQjOQjc ahf(B, (3HQGhfs ((3GdbGgQI(B:s (3eQcR GdNHQGJ GdegfjI dEOGQI Hejc(B,s, 2000)
(3GdJLOjO hMOg dG jcaj(B- (3JGQjN GdHMK hGdJWhjQ GdUfGYj(B- (3gd JLGhR GdHMK hGdJWhjQ GdeOi (B-(3GdSbhW aj aN GdJUYjO(B- (3BKGQ hfJGFL aN GdJYLjd(B- (3GSJfJGLGJs
Keywords: (3GdEOGQIs; (3af GdEOGQIs